Generative design: information flow between genetic algorithm and parametric design in a steel structure construction - Cruz, Renato Godoi da; Arcipreste, Cláudia Maria; Pinheiro, Rafael Lemieszek; Ribas, Rovadávia Aline de Jesus (Ambiente Construído, 2021)
This paper describes the construction of an information flow that combines parametric modelling and genetic algorithms to optimise both the total weight of a structured steel roof and the shape of its surface to maximise the generation potential of photovoltaic energy. Through the systematisation of a design process using genetic algorithms integrated with generative design as an architectural design method, architects can work with problem parameterisation, going one step further than the mere formal proposition of solutions. As a result, we present a process in which there is a dialogical relationship between the architect and project in a continuous flow of information in the initial steps of the design process, guided by predefined optimisation objectives. Therefore, it is relevant to note that the designer accepts a reduced creative control over the final shape in favor of control over the core principles that constitute the optimisation algorithms. An approach that involved the designer in a process of post computational processing evaluations is also highlighted, giving him better support to discuss and analyze the design options.